The Effect of Green Operations Strategy in Environmental Performance: The Interactive Role of Environmental Human Capital (Analytical Study in the Basra Paper Manufactory) - Prof. Dr. Hashim Nayef Hashim Al-Hachim; Adnan Saad Tuama Al-Sukaini (Scholars Digest Publishing, 2023)
The study aims to reveal the relationship between green operations strategy as an independent variable and environmental human capital as an interactive variable to achieve environmental performance as a dependent variable. The main problem of this study was the question: What is the impact of green operations strategy on environmental performance through the interactive variable environmental human capital? the importance of the study stems from its focus on ( the industry sector) in general and the paper industry in particular because of its role in supporting the economic activity of the country. study leads to a set of conclusions, foremost of which is that the support of the senior management is an essential element for achieving an appropriate environmental performance, through its support and support for the individuals working in the factory and the provision of training programs to upgrade the level of capabilities and skills they enjoy and create a level of awareness among them of the need to achieve a good environmental performance to ensure survival and growth for the factory.
Keywords: green operations strategy, environmental human capital, environmental performance.